95.9k views
3 votes
Determine if "h=3" is a solution.
3h=2(h+2)-1

User Ethanpil
by
6.2k points

2 Answers

3 votes

Answer:

Explanation:

3h=2(3+2)-1

3h=6h+4-1

3h=6h+3

-6h=-6h+3

-3h=3

-3h/-3=3/-3

h=-1

User Rui Peres
by
6.7k points
2 votes

Answer:

Yes is a solution

Explanation:

3h = 2(h+2)-1

We replace h=3

3*3 = 2(3+2) - 1

Solve

9 = 2(5)-1

9 = 10 - 1

9 = 9

Is correct h= 3

when we manage to find the same value on both sides of equality it means that the value entered is a possible option

User Nafeesa
by
5.7k points